Pretarsal structures in Leiodidae and Agyrtidae (Coleoptera, Staphylinoidea). (11th June 2017) - Gnaspini, Pedro; Antunes‐Carvalho, Caio; Leschen, Richard A. B.
Abstract: We analysed pretarsal characters of 87 species of Leiodidae (including 10 cholevines and representatives of all tribes and ca. 60% of the genera of non‐cholevines), five species of Agyrtidae, and nine representatives of outgroup taxa (Hydraenidae, Staphylinidae, Hydrophilidae, and Histeridae) using scanning electron microscopy. We focused our observations on the architecture of the empodium (including the sclerites and associated setae), the shape and composition of the medial projection of the distal margin of the terminal tarsomere, and the armature of the claws, which were considered a promising source of information for delimiting supraspecific taxa in our previous study. We identified several diagnostic features and recognize potential synapomorphies at the tribal, subtribal and generic levels. The internal systematic arrangement and/or even the monophyletic status of most of the subfamilies of Leiodidae (Camiarinae, Catopocerinae, Leiodinae, and Platypsyllinae) are challenged. We identified potential synapomorphies for Camiarinae (Camiarini and Agyrtodini) and Leiodinae. The non‐monophyly of Cholevinae is possible because part of the tribe (Anemadini, Eucatopini, and Oritocatopini) shares potentially apomorphic features with Leiodinae (e.g., a triangular medial projection with a diagonal row of conical spines), whereas another part (Leptodirini and Ptomaphagini) shares a potentially apomorphic feature with Coloninae and Platypsyllinae (a typical medial projection with two distinct triangular projections). Abstract : Comparative morphology of the empodium and medial projection of distal margin of the apical tarsomere and armature of tarsal claws in leiodids and related taxa indicate a wealth of new diagnostic features and potential synapomorphies for family‐groups.